Análise tipológica dos edifícios multifamiliares no bairro do Farol - Maceió / AL (2000-2010) - Santos, Fabiane Jhoralina de Oliveira (2016)
The construction of apartment buildings has skyrocketed in recent decades on Farol District in Maceió/AL. This type of housing has similarities and significant programmatic changes. This work aims to identify the recurring architectural typologies in building multifamily buildings recorded in Farol District in Maceió- AL. The methodology comprised a cadastral survey in the Department of Control and Urban Gathering (SMCCU), where they found 25 buildings, distributed in two residential areas in which it divides the Farol District. With this collection, an analysis based on internal and external spatial organization of parameters were performed with reference variables proposed by Brandão (2002). Analyses subdivided into two steps: (1) typology of buildings, where were observed: the building's relationship with the lot, volumetric aspects and internal configuration and (2) type of the internal spatial arrangement of the apartment, watching number of environments, sizing and geometry; and internal spatial arrangement, these types were observed the link between sectors and the connection of the sectors with the outside. The results showed that the buildings in relation to the volumetric start to present variation of the rectangular prism with addition and subtraction operations, maintains stilts configuration and offsets the limits of the lots. The use of the common areas for leisure is consolidated in the sample universe, because of the demand, because this activity before performed in public spaces of the city, tends to self isolation due to the lack of public safety. The analyzes of the apartments show that the most frequent type was that of three bedrooms and three bathrooms with maid. Then the typology four bedrooms and three bathrooms. It was found, as in previous surveys, the permanence batting plants and balconies; existence hall at the entrance of the suites, etc. end of separation between kitchen and service and integration between the living and dining room; big difference in the areas of rooms, with less variation in the dorms. The systematization of the results recorded major typological features, identifying trends in the architectural configuration of apartment buildings, with the aim of contributing to the improvement of the human habitat.